(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ritonga AW, Mukhlisin, Sutjahjo SH. 2025. Estimation of genetic parameters and path analysis in sweet-waxy corn (Zea mays var. ceratina). Biodiversitas 26: 879-889. Waxy corn is commonly consumed as a staple food in Eastern Indonesia. The development of hybrid sweet-waxy corn is crucial for enhancing its quality and productivity. The information about genetic parameters and yield-related traits is essential in plant breeding programs to obtain high-yielding hybrids. This study aimed to determine the genetic variability, heritability, and yield-related traits in sweet-waxy corn hybrids. This research was carried out at two locations, Bogor and Lampung, from September 2023 to February 2024. Fifteen sweet-waxy corn hybrids were sown in a randomized complete block design with three replicates. The recorded data were plant height, ear height, stem diameter, leaf width, leaf length, the number of leaves, the number of kernels per row, the number of rows per ear, ear diameter, ear length, and ear weight without husk. The findings revealed that the G1, G7, and G12 hybrids demonstrated superior yield traits at both locations. All observed traits demonstrated high heritability, with the exception of stem diameter and the number of kernels per row. The phenotypic and genotypic coefficients of variation were within the moderate to high, with percentages ranging from 4.15% to 16.69%. Correlation analysis suggested a positive association between ear weight without husks with the other traits. Ear diameter, ear length, and the number of kernels per row had highly positive direct effects on the ear weight without husks, while leaf width had a strong indirect effect through ear diameter (0.415). Thus, these traits may be utilized as selection criteria in corn breeding programs.